Unconscionability and the clash between contractual justice and freedom of contract in Malaysia - Abdullah, Mohd Faiz; Ab Rahman, Rozanah (Billion Brains, 2011)
Malaysian courts apply conventional principles in determining cases involving contract law. They tend to emphasise the importance of form and procedure over substance and are inclined to enforce a contract as long as it satisfies the basic requirements of validity. The courts are averse to intervening, let alone declare an entire contract nugatory. The doctrine of unconscionability, though much in use in England and other common law jurisdictions appears retarded in Malaysia’s jurisprudence, caught in the clash between contractual justice and freedom of contract. This paper argues in favour of the former and states the case as to why courts should administer justice, and just law.